Sistem Informasi Pencatatan Hafalan Al-Qur’an dan Iqro Berbasis Website pada TPA Pesayidan Kota Cirebon - Nurpuriani, Zahrina; Nurpatimah, Suci; Asfi, Marsani (DPPM Universitas Pelita Bangsa, 2024)
This research aims to design and develop a web-based information system for recording Quran memorization and Iqro at TPA Pesayidan, Kota Cirebon. The system is expected to facilitate the process of recording and monitoring students' memorization progress and to reduce the errors commonly encountered with manual methods, specifically conventional record-keeping in achievement books. The primary issues addressed include inaccuracies and inefficiencies in managing memorization data using traditional methods. To address these problems, the research employed direct observation, literature review, system design analysis, system development, implementation, and system testing. The resulting information system allows educators to record, monitor, and evaluate students' memorization more effectively and efficiently. System testing indicates that the web-based system significantly improves the accuracy and efficiency of managing memorization data and accelerates the evaluation process for teachers. In conclusion, the implementation of this system has the potential to enhance the quality of learning and provide significant benefits to TPA administrators in managing students' memorization data. The results of system testing demonstrate the success in overcoming the limitations of manual recording with a more structured and measurable solution